The Time of Politics and the Politics of Time: Exploring the Role of Temporality in British Constitutional Development During the Long Nineteenth Century - Vieira, Ryan A. (My University, 2011)
“The Time of Politics and the Politics of Time: Exploring the Role of Temporality in British Constitutional Development during the Long Nineteenth Century,” studies the role of time in the development of Britain’s liberal democracy. Conceptually, it explores time both as a structure that the procedural framework of the British Parliament produced and as an historical perception that the technological culture of modernity constructed. In both cases, the study focuses on the constitutional significance of perceived fluctuations within the scarcity of political time as well as imagined changes in the pace and continuity of history. Methodologically, I use these conceptualizations of time in order to examine the intersection of four seemingly disparate political phenomena in Victorian and Edwardian Britain: namely, the perceived expansion of democracy, the instrumentalization of rationality in political culture, the devaluation of deliberative practices as forms of political action, and the rise of mass political dissatisfaction with the efficiency of Parliament.﻿
Keywords: Time; Parliament; Acceleration; Efficiency; Temporality; Liberalism; National Efficiency; Cultural History; Intellectual History; Political History; Political Theory; Cultural History